2017
DOI: 10.1111/imr.12483
|View full text |Cite
|
Sign up to set email alerts
|

Germline‐targeting immunogens

Abstract: Summary In 2009 D. Dimitrov’s group reported that the inferred germline (iGL) forms of several HIV-1 broadly neutralizing antibodies (bNAbs), did not display measurable binding to a recombinant gp140 Env protein (derived from the dual-tropic 89.6 virus), which was efficiently recognized by the mature (somatically mutated) antibodies (1). At that time a small number of bNAbs were available, but in the following years, the implementation of high-throughput B cell-isolation and sequencing assays (2) and of screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
127
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(131 citation statements)
references
References 133 publications
(402 reference statements)
3
127
1
Order By: Relevance
“…These interactions initiate and orchestrate the trimerization process, but the stability of the trimer as a whole is also influenced by other interactions that include ones involving the apex. A more precise understanding of these stabilizing interactions may be useful for improving trimer stability in general and particularly in the context of germ line bNAb-targeting trimers that may need conformational adjustments to confer the desired antigenicity profile (30,58,59).…”
Section: Discussionmentioning
confidence: 99%
“…These interactions initiate and orchestrate the trimerization process, but the stability of the trimer as a whole is also influenced by other interactions that include ones involving the apex. A more precise understanding of these stabilizing interactions may be useful for improving trimer stability in general and particularly in the context of germ line bNAb-targeting trimers that may need conformational adjustments to confer the desired antigenicity profile (30,58,59).…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Wardemann et al reported that BCRs cloned from mature follicular (Fo) human B cells, in contrast to immature BM B cells, exhibit little DNA-reactivity and poly-reactivity (defined as binding to more than one antigen among a panel including ssDNA, dsDNA, insulin, and LPS), but a significant fraction (20%) can bind cytoplasmic antigens (assessed by immunofluorescent staining of permeabilized cells using cloned Abs). 8,9 Wardemann et al reported that BCRs cloned from mature follicular (Fo) human B cells, in contrast to immature BM B cells, exhibit little DNA-reactivity and poly-reactivity (defined as binding to more than one antigen among a panel including ssDNA, dsDNA, insulin, and LPS), but a significant fraction (20%) can bind cytoplasmic antigens (assessed by immunofluorescent staining of permeabilized cells using cloned Abs).…”
Section: S Elf-re Ac Tivit Y In the Mature B Cell Repertoirementioning
confidence: 99%
“…Various hypotheses about the nature of protective immunity are being explored using a variety of vaccine designs in animal models and human volunteers (Escolano et al, ; Haynes & Mascola, ; Korber, Hraber, Wagh, & Hahn, ; Safrit et al, ). One active area of research is to identify ways to induce broadly neutralizing antibodies (bNAbs) that target the envelope glycoprotein (Env) trimer on the surface of infectious HIV‐1 virions (Haynes & Mascola, ; Sanders & Moore, ; Stamatatos et al, ). Eliciting bNAbs is an attractive concept because of their ability to counter the extensive sequence diversity that is a critical aspect of the global HIV‐1 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Although low titers of NAbs against heterologous Tier‐2 viruses are occasionally elicited, SOSIP.664 and improved trimers have not induced bNAbs in the above species (Cheng et al, ; Chuang et al, ; de Taeye et al, ; Klasse et al, ; Sanders & Moore, ; Sanders et al, ; Torrents de la Pena et al, ). Nonetheless, native‐like trimers are key components of more sophisticated immunogen design and delivery programs aimed at eventually eliciting bNAbs (Medina‐Ramirez et al, ; Sanders & Moore, ; Stamatatos et al, ; Ward & Wilson, ).…”
Section: Introductionmentioning
confidence: 99%